THE CORRELATION BETWEEN STUDENTS’ SPEAKING ABILITY AND THEIR TENSES MASTERY - Anam, Mukhtarul; Fatih akbar khoirudin (E-Link Journal, 2024)
The study aimed to find out the correlation between students' speaking ability and their tenses mastery. This study was conducted at Abu Huroiroh Dormitory Sunan Drajat Islamic Boarding School. This study employed correlational method. The population of this study was 146 students and the sample was 30 students of Abu Huroiroh Dormitory. The samples were picked randomly using random sampling method. There were two instruments in this study, oral test and tenses test. The oral test was used to find out the students’ grammar and fluency. Meanwhile, the tenses test was used to find out the students’ mastery in simple present, simple past, and simple future. This study found out that the mean score of students' speaking ability was categorized as fair (62) while the mean score of the students' tenses mastery was categorized as poor (44). The correlation rate from both variable (rxy) was 0,683 and it was categorized in 'substantial' level. also, the rxy (0,683) was bigger than r table (0,374). it could be concluded that there was positive and significance correlation between students' speaking ability and their tenses mastery.